Pathophysiology of anemia in chronic kidney diseases: A review - Zadrazil, Josef; Horak, Pavel (Biomedical papers, 2015)
Backgroud. Anemia is one of the laboratory and clinical findings of chronic kidney diseases (CKD). The presence of anemia in patients with CKD has a wide range of clinically important consequences. Some of the symptoms that were previously attributed to reduced renal function are, in fact, a consequence of anemia. Anemia contributes to increased cardiac output, the development of left ventricular hypertrophy, angina, and congestive heart failure. According to current knowledge, anemia also contributes to the progression of CKD and is one of the factors that contribute to the high morbidity and mortality in patients with chronic renal failure and their reduced survival.Methods: MEDLINE search was performed to collect both original and review articles addressing anemia in CKD, pathophysiology of renal anemia, erythropoiesis, erythropoietin, iron metabolism, inflammation, malnutrition, drugs, renal replacement therapy and anemia managementConclusion: The present review summarized current knowledge in the field of the pathophysiology of renel anemia. Understanding the pathophysiology of anemia in CKD is crucial for the optimal treatment of anemia according to recent clinical practice guidelines and recommendation, and correct recognition of causes of resistence to treatment of erythropoietin stimulating agents (ESA).
Keywords: anemia; chronic kidney diseases; erythropoietin; irone metabolism; erythropoiesis